Exploring factors affecting postgraduate student retention when enrolling via accreditation for prior experiential learning (APEL) - Nooraini Youp,; Norazah Mohd Suki, (2019)
Retaining of postgraduate Masters Degree students’ are often scrutinised, as are subsets of graduate students such as under represented populations. However, little emphasis is placed on the largest component of graduate education, namely, students enrolled in master’s degree programmes. When a student registers in an academic programme at a university, both enter into a partnership intended to culminate with the student earning a masters degree awarded by the institution. Both have responsibilities in this partnership, students must put in the effort to complete the intended programme successfully, while institutions must provide appropriate resources to allow students to succeed. An increasing number of students are enrolling in the Master Degree programmes through Accreditation of Prior Experiential Learning (APEL) in Open University Malaysia (OUM). Although students enrol into a programme for a variety of reasons, their completion rate for the Masters programme does not commensurate with the initial enrolment numbers. The purpose of this research is to explore factors affecting postgraduate students’ retention when enrolling via accreditation of prior experiential learning (APEL) in Open University Malaysia. Results will be analysed through a series of descriptive statistics of factors like; 1) self-motivation and 2) academic performance that contributes to the students’ commitment to stay in their programmes. This study is important as it aids open distance learning institutions to remain sustainable.